Construction risk management - Wong, Keng Lian (2000)
There are three main constraints namely as cost, time and quality in every construction project. The main causes of the failure to achieve the budgeted cost, planned completion date and desired quality is due to uncertainties arise in the entire project life cycle. Hence, risk management has been introduced to assist project management team to achieve the target. The aim of the research is to introduce the Risk Management process and provide useful information on managing risk to the local construction industry. This research also seeks to help the project management team to make a quality decision w hen expose to different type of risk. The research consists of the analysis of the concept of risk in investment; the study of risk in construction project; the examination of the Formal Risk Management process and the survey of the existence of Risk Management process in local Construction industry. The five main component of Formal Risk Management are Risk Identification, Risk Classification. Risk Analysis, Risk Attitude and Risk Response are introduced to enabling parties involve in the construction project understand, identify potential risk and to system atically analyse and manage it using the four components divided in the risk response stage. The four main decisions on managing risk are transfer, retain, avoid and reduce the risk. From the survey, the respondents indicate the less common use of Formal risk Management Process. The analysis signalled the existence of risk management process is decision making, not in well organised structured.